Effect of Nutritional Status and Anemia in the Wound Healing Process of Post Cesarean Section Patients - Nithya, DJ (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Sectio Caesarea is an action to deliver a baby weighing more than 500 grams, through an incision in the intact uterine wall. The increase in cesarean section rates has not been able to improve the final condition of the neonate and can even increase the risk of maternal mortality and morbidity. The purpose of this study was to determine the Relationship between Anemia and Nutritional Status with the Wound Healing Process in Postoperative Sectio Caesarea Patients in the Hospital Postpartum Room. This study was conducted based on analytical research methods using a cross-sectional approach. the results of the Chi-square test analysis obtained a value of ρ value = 0.001 (ρ < 0.05), where Ha is accepted and H0 is rejected, so there is a significant relationship between Anemia and the Wound healing Process in Postoperative Sectio Caesarea patients in the Hospital Postpartum Room.